2010
DOI: 10.1063/1.3506690
|View full text |Cite
|
Sign up to set email alerts
|

Bennett clocking of nanomagnetic logic using multiferroic single-domain nanomagnets

Abstract: The authors show that it is possible to rotate the magnetization of a multiferroic (strain-coupled two-layer magnetostrictive-piezoelectric) nanomagnet by a large angle with a small electrostatic potential. This can implement Bennett clocking in nanomagnetic logic arrays resulting in unidirectional propagation of logic bits from one stage to another. This method of Bennett clocking is superior to using spin-transfer torque or local magnetic fields for magnetization rotation. For realistic parameters, it is sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
118
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 18 publications
2
118
0
1
Order By: Relevance
“…Popular approaches include passing a spin current through the soft layer to generate a spin transfer torque 2-7 or spin orbit torque [8][9][10][11] or domain wall motion [12][13] . Other approaches involve using voltage controlled magnetic anisotropy 14 , magnetoelectric effects 15-17 , magnetoionic effects 18 and magnetoelastic effects [19][20][21][22][23][24][25] . Unfortunately, generation of a spin current requires passing a charge current through a resistor that dissipates excessive energy, making the spin-current based schemes relatively energy-inefficient 26,27 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Popular approaches include passing a spin current through the soft layer to generate a spin transfer torque 2-7 or spin orbit torque [8][9][10][11] or domain wall motion [12][13] . Other approaches involve using voltage controlled magnetic anisotropy 14 , magnetoelectric effects 15-17 , magnetoionic effects 18 and magnetoelastic effects [19][20][21][22][23][24][25] . Unfortunately, generation of a spin current requires passing a charge current through a resistor that dissipates excessive energy, making the spin-current based schemes relatively energy-inefficient 26,27 .…”
mentioning
confidence: 99%
“…One magnetoelastic scheme, the so-called "straintronic" switching, involves rotating the magnetization of a magnetostrictive soft layer with mechanical strain generated by applying a voltage across an underlying piezoelectric layer with a suitable arrangement of electrodes [28][29][30] . The voltage generates strain in the piezoelectric, which is partially or completely transferred to the elliptical magnetostrictive soft layer,and rotates magnetization by the Villari effect [19][20][21][22][23][24][25] . It has been predicted theoretically that large angle (~90 o ) rotation in ~100 nm feature sized nanomagnets made of highly magnetostrictive materials (Terfenol-D, FeGa) will dissipate only ~1 aJ of energy to occur in ~1 ns [31][32][33] .…”
mentioning
confidence: 99%
“…This strain/stress can cause the magnetization of the magnetostrictive layer to rotate by a large angle [16], which has been demonstrated in recent experiments, although not at the nanoscale [17]. These rotations are sufficiently large to fulfill the requirements of Bennett clocking in logic chains [13]. In the specific configuration discussed in this paper, the voltage strains the piezoelectric layer via the d 31 coupling…”
Section: Introductionmentioning
confidence: 66%
“…Recently, we showed that local clocking of NML can be implemented by applying a small voltage to a nanomagnet made of multiferroics [13]. Such a nanomagnet consists of two elastically coupled piezoelectric and magnetostrictive layers as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation